Prokaryotic Diversity and Composition of Sediments From Prydz Bay, the Antarctic Peninsula Region, and the Ross Sea, Southern Ocean - Li, Jiang; Gu, Xiaoqian; Gui, Yuanyuan (Frontiers in Microbiology, 2020)
The V3–V4 hypervariable regions of the 16S ribosomal RNA gene were analyzed to assess prokaryoticbacterial diversity and community compositions within 19 surface sediment samples collected from three different regions (depth: 250–3,548 m) of Prydz Bay, the Antarctic Peninsula region, and the Ross Sea. In our results, we characterized 1,079,7,09 clean tag sequences representing 43,227 operational taxonomic units (OTUs, 97% similarity). The prokaryoticbacterial community distribution exhibited obvious geographical differences, and the sequences formed three distinct clusters according to the samples’ origins. In general, the biodiversity of Prydz Bay was higher than those of the Antarctic Peninsula region and the Ross Sea, and there were similar prokaryoticbacterial communities in different geographic locations. The most dominant clades in the prokaryoticbacterial communities were Proteobacteria, Bacteroidetes, Thaumarchaeota, Oxyphotobacteria, Deinococcus-Thermus, Firmicutes, Acidobacteria, Fusobacteria, and Planctomycetes, but unique prokaryoticbacterial community compositions were found in each of the sampling regions. Our results also demonstrated that the prokaryoticbacterial diversity and community distribution were mainly influenced by geographical and physicochemical geophysicochemical factors, such as geographical distance, Ba, Zn, V, Na, and K, contents, and water depth, and especially geographical distance (longitude variation of sample location) and Ba ion content. Moreover, geochemical factors such as nutrient contents (TC, P, and Ca) also played important roles in bacterial diversity and community distribution. This represents the first report that Ba ion content has an obvious effect on prokaryoticbacterial diversity and community distribution in Southern Ocean sediments.